Synthesis and antifungal activity of 1,5-disubstituted-1,2,3-triazole containing fluconazole analogues - Pore, Vandana S.; Jagtap, Manisha A.; Agalave, Sandip G.; Pandey, Atindra K.; Siddiqi, Mohammad I.; Kumar, Vikash; Shukla, Praveen K. (Medchemcomm, 2012)
Fluconazole based novel mimics containing 1,5-disubstituted 1,2,3-triazoles were synthesized by using Ru catalysed 1,3 dipolar cycloaddition. All the newly synthesized compounds and pure enantiomers were more potent than fluconazole against Candida albicans. Docking of 9A and 9B showed different conformation in the active site of Cyp51 of Candida albicans. The more active compounds 2 and 2A did not exhibit any toxicity up to 3.12 mu g mL(-1) against mammalian cell line L929.

Design and synthesis of new fluconazole analogues - Pore, Vandana S.; Agalave, Sandip G.; Singh, Pratiksha; Shukla, Praveen K.; Kumar, Vikash; Siddiqi, Mohammad I. (Organic & Biomolecular Chemistry, 2015)
We have synthesized new fluconazole analogues containing two different 1,2,3-triazole units in the side chain. The synthesis of new amide analogues using a variety of acids is also described. All the compounds showed very good antifungal activity. A hemolysis study of the most active compounds 6e and 13j showed that both compounds did not cause any hemolysis at the dilutions tested. These compounds did not exhibit any toxicity to L929 cells at MIC and lower concentrations. In the docking study, the overall binding mode of 6e and 13j appeared to be reasonable and provided a good insight into the structural basis of inhibition of Candida albicans Cyp51 by these compounds.